Call for worldwide withdrawal of tiotropium Respimat mist inhaler. (9th November 2012) - Beasley, Richard; Singh, Sonal; Loke, Yoon K; Enright, Paul; Furberg, Curt D
Abstract : Tiotropium Respimat mist inhaler increases the risk of death